Manusia Sebagai Animal Educandum Dalam Perspektif Pendidikan Nativisme: Kajian Kualitatif Deskriptif Naratif - Elvira Meilinda Rosa; Arief Kuswidyanarko; Henni Riyanti (Universitas Pakuan, 2026)
HUMAN BEINGS AS ANIMAL EDUCANDUM IN THE PERSPECTIVE OF NATIVIST EDUCATION: A QUALITATIVE DESCRIPTIVE NARRATIVE STUDY This article discusses human beings as Animal Educandum from the perspective of nativist education using a qualitative descriptive narrative approach. The study is grounded in the importance of understanding humans as beings who possess innate potential while also requiring education to develop their humanity. Human children are not born independent; they enter life in a weak, dependent, and unfinished condition that requires assistance from adults and the surrounding social environment. Therefore, education is understood as a process of guidance that helps children recognize, direct, and develop the potential they have brought since birth. This study aims to explain the concept of human beings as Animal Educandum, the meaning of human children as beings who need assistance, and education from the perspective of nativism. The method used is qualitative descriptive narrative through a literature review of relevant sources on educational philosophy, human nature, child development, and nativist theory. The findings show that human beings as Animal Educandum are characterized by educability, the need for guidance, and the potential to grow through educational processes. Human children need assistance because they do not yet possess complete physical, social, emotional, intellectual, and moral readiness. From the nativist perspective, education does not create potential from nothing, but serves to direct innate potential so that it can develop optimally. Understanding humans as educational beings can help teachers and parents design humane guidance. Education should consider children’s talents, dispositions, character, and needs, so learning is not limited to academic achievement but supports the formation of a personality.